2021
DOI: 10.3390/ijerph182312656
|View full text |Cite
|
Sign up to set email alerts
|

Workability in the Ageing Workforce—A Population-Based Cross-Sectional Study

Abstract: Background: The purpose of this study was to investigate the impact of age, musculoskeletal pain and ergonomic exposure on workability in the oldest group of workers. Methods: The study was a population based cross-sectional survey. The study population comprised citizens born between 1952–1966, living in Esbjerg municipality ultimo 2016 (n = 23,463). A questionnaire was sent electronically or by mail. The analysis included the working population only. A stereotype logistic regression was used with the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
(97 reference statements)
1
10
0
Order By: Relevance
“…These environmental factors that allow a balance between work and health are important for older manual workers. Ageing manual workers face a risk of lacking this balance because they are at the crossroads of possible decreasing work ability due to age [ 18 ] and the physical demand embedded in their work positions [ 19 ]. A study done in the Netherlands found that manual labour, namely materials handling, was one of the most important risk factors for moderate and long durations of sick leave [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These environmental factors that allow a balance between work and health are important for older manual workers. Ageing manual workers face a risk of lacking this balance because they are at the crossroads of possible decreasing work ability due to age [ 18 ] and the physical demand embedded in their work positions [ 19 ]. A study done in the Netherlands found that manual labour, namely materials handling, was one of the most important risk factors for moderate and long durations of sick leave [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This present study is part of a population based crosssectional survey conducted in the 4 th quarter of 2017 -2 nd quarter of 2019 in Esbjerg municipality [6]. The methodology has been described elsewhere [6].…”
Section: Methodsmentioning
confidence: 99%
“…This present study is part of a population based crosssectional survey conducted in the 4 th quarter of 2017 -2 nd quarter of 2019 in Esbjerg municipality [6]. The methodology has been described elsewhere [6]. In brief, a comprehensive questionnaire was constructed, based on validated questionnaires, focusing on health status, musculoskeletal pain, perceived stress, ergonomic exposure and workability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations